Pengaruh Imunisasi terhadap Tingkat Morbiditas dan Status Gizi (IMT/U) pada Balita di Wilayah Kerja Puskesmas Polokarto Sukoharjo - Maysaroh, Siti, Luluk Ria Rakhma, S.Gz., M.Gizi, Siti Zulaekah, A., M.Si (2016)
The high of infant and toddlers mortality in Indonesia causes decreasing degrees of public health. Highest cause of mortality is the high of morbidity. Morbidity is an important health problem especially for children under 5 years old because in this age the immune is not fully formed. Immunization is an effort to give the immune system towards infant and children to prevent a specific disease as of not be susceptible of infection which will affect the nutritional status. The purpose of this research is to determine the effect of immunization on morbidity and nutritional status (BMI/A) in infants in the working area of Puskesmas Polokarto, Sukoharjo. The type of research is an observational descriptive research using cross sectional design. Numbers of samples are 34 toddlers which recruited using simple random sampling. The data collection of immunization and morbidity (days of diarrhea and acute respiratory infection) were obtained by interview using questionnaires, data of nutritional status were obtained by anthropometric measurements. Independent t-test was used to analyze the nutritional status (BMI/A) variable and Mann Whitney was used to analyze the morbidity variable. Result of the bivariate analysis shows that there are no significant immunization effect on days of diarrhea (p=0,062), immunization effect on days of ARI (p=0,289) and immunization effect on nutritional status (p=0,305) in infants with complete and incomplete immunization. The conclusion of this research is there are no significant effect of immunization with morbidity and nutritional status (BMI/A).